2005
DOI: 10.4040/jkan.2005.35.8.1433
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Suicidal Ideation for Adolescents by Gender

Abstract: Purpose. The purposes of this study were 1) to examine the differences in suicidal ideation and psychological variables by gender, 2) compare the contribution of demographic-behavioral variables and psychosocial variables in explaining the variance in suicidal ideation, and 3) identify the most important predictors of suicidal ideation for male adolescents and female adolescents.Methods. The subjects consisted of 271 male adolescents and 230 female adolescents. Data were collected through self-report questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
24
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 24 publications
4
24
0
1
Order By: Relevance
“…This research has identified a range of risk factors related to family functioning and parent-child relationships during childhood and adolescence that have been found to predict later suicidal behavior. These factors include: parental disharmony, separation or divorce [4,11]; parental psychopathology such as substance abuse [4,10,14,[19][20][21]; a family history of suicidal behavior [17,20,21]; impaired parent-child relations, poor attachment, and bonding [6,7,14,15,17,18,21]; and exposure to physical and sexual abuse [14, 17-19, 22, 23]. In general, these findings suggest that young people exposed to adverse, dysfunctional or abusive childhood environments are at a significantly greater risk for subsequent suicidal behavior.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This research has identified a range of risk factors related to family functioning and parent-child relationships during childhood and adolescence that have been found to predict later suicidal behavior. These factors include: parental disharmony, separation or divorce [4,11]; parental psychopathology such as substance abuse [4,10,14,[19][20][21]; a family history of suicidal behavior [17,20,21]; impaired parent-child relations, poor attachment, and bonding [6,7,14,15,17,18,21]; and exposure to physical and sexual abuse [14, 17-19, 22, 23]. In general, these findings suggest that young people exposed to adverse, dysfunctional or abusive childhood environments are at a significantly greater risk for subsequent suicidal behavior.…”
mentioning
confidence: 99%
“…Most studies which examined the associations between measures of social disadvantage and suicide or suicide attempts have reported an increased risk of suicidal behavior among individuals from socially disadvantaged backgrounds characterized by low socioeconomic status (SES), limited educational achievement, low income, and poverty [3,7,8,[14][15][16][17][18]. Considerable research has focused on the extent to which exposure to adverse, dysfunctional or abusive family and/or childhood circumstances is associated with an increased risk of suicidal behavior in Korean youth [14,15]. This research has identified a range of risk factors related to family functioning and parent-child relationships during childhood and adolescence that have been found to predict later suicidal behavior.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2;2016 substance abuse and delinquency (Sun & Shek, 2010). Life satisfaction is also a significant predictor of the development of suicidal ideation in adolescents (Park, Koo, & Schepp, 2005). Past study which was conducted among 13 to 18 years old adolescents even revealed that higher suicide attempt was significantly related to lower level of life satisfaction .…”
Section: Introductionmentioning
confidence: 99%
“…긍정적인 발달의 현상과 관련된 요인을 밝히는 것을 주요 과제 로 하고 있으며 (Simnton & Baumeister, 2005) 청소년의 자살과 폭력 행동의 주요 위험요인으로 공격성을 들 수 있다 (Oh, 2005;Park, Koo, & Schepp, 2005;Smochek et al, 2000). 청소년의 공격성은 자신에게로 향할 때 자살행 위로 이어질 수 있지만, 타인으로 향할 때 폭력행동을 유발할 수 있다 (Plutchik, 1995).…”
unclassified